IMPLEMENTATION OF FUZZY LOGIC CONTROLLERS TO MAINTAIN WATER TEMPERATURE IN HYDROPONICS NFT FOR LOLLO VERDE LETTUCE (LACTUCA SATIVA L.) - FAUZAN, MOHAMAD NURKAMAL; SAPTARINI, NYI MEKAR (International Journal of Applied Pharmaceutics, 2021)
Objective: The purpose of this study was to maintain the nutritional water temperature in the range of 25-27 °C for Lollo Verde lettuce (Lactuca sativa L.). Methods: The method was the Fuzzy Logic Mamdani (FLM) with two inputs, i.e. real time clock and temperature. The output was crisp speed PWM with the center of area method. Results: The results showed that Fuzzy logic was succeeded in reducing water temperature in the NFT system from 28-32 °C to 26-27 °C, with an average delta of 3.5 °C. Fuzzy logic maintained the nutrient water temperature in the Lollo Verde lettuce with an average of 26.57±0.5 °C. Water temperature affected the yield of Lollo Verde lettuce. Conclusion: The yield of NFT FLM system was better compared to the conventional NFT system.